Histopathology of the rice root-knot nematode, Meloidogyne graminicola, on Oryza sativa and O. glaberrima - Cabasan, Ma. Teodora Nadong; Kumar, Arvind; Bellafiore, Stéphane; De Waele, Dirk (Brill, 2014)
The root-knot nematode,Meloidogyne graminicola, can cause substantial rice yield losses. Understanding the mechanisms of resistance to this nematode species in known resistant rice genotypes may help to improve rice genotypes, aiming at developing and implementing environment-friendly and cost-effective nematode management strategies. Using susceptible and resistant rice genotypes, a comparative analysis of histological response mechanisms was made during two phases of the nematode colonisation:i) root penetration; andii) subsequent establishment and development byM. graminicolasecond-stage juveniles (J2). Two types of defence response mechanisms could be distinguished in the resistant rice genotypes. The early defence response consisted of a hypersensitive response (HR)-like reaction in the early stage of infection characterised by necrosis of cells directly affected by nematode feeding. This HR-like reaction was observed only in theM. graminicola-resistantOryza glaberrimagenotypes and not in theM. graminicola-susceptibleO. sativagenotypes. The late defence response took place after the induction of giant cells by the J2. Giant cells usually collapsed and degenerated before J2 developed into adults. Structural features of the roots of the susceptibleO. sativashowed greater root and stele diam. and cortex thickness than the resistantO. glaberrimagenotypes. Desired features of plants with resistance toM. graminicolaelucidated in this study can be used for selection of plants for breeding programmes.